2017
DOI: 10.1371/journal.pone.0177749
|View full text |Cite
|
Sign up to set email alerts
|

Human plasma metabolomics in age-related macular degeneration (AMD) using nuclear magnetic resonance spectroscopy

Abstract: PurposeTo differentiate the plasma metabolomic profile of patients with age related macular degeneration (AMD) from that of controls, by Nuclear Magnetic Resonance (NMR) spectroscopy.MethodsTwo cohorts (total of 396 subjects) representative of central Portugal and Boston, USA phenotypes were studied. For each cohort, subjects were grouped according to AMD stage (early, intermediate and late). Multivariate analysis of plasma NMR spectra was performed, followed by signal integration and univariate analysis.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
88
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(104 citation statements)
references
References 39 publications
13
88
3
Order By: Relevance
“…In ophthalmology, metabolomics has been used to study various eye diseases including glaucoma [10][11][12][13][14][15][16] , age-related macular degeneration [17][18][19] , diabetic retinopathy [20][21][22] , keratoconus [23] , refractive error [24,25] , retinal detachment [26] , uveitis [27,28] , dry eye [29,30] , and other ocular surface diseases [31] . Analyses have been performed on tear fluid [23,[29][30][31][32] , aqueous humor [24,25,33,34] , vitreous humor [20,26,27,35,36] , cornea [37][38][39] , conjunctiva [40] , and lens [41,42] samples.…”
Section: Metabolomics In Ophthalmologymentioning
confidence: 99%
See 1 more Smart Citation
“…In ophthalmology, metabolomics has been used to study various eye diseases including glaucoma [10][11][12][13][14][15][16] , age-related macular degeneration [17][18][19] , diabetic retinopathy [20][21][22] , keratoconus [23] , refractive error [24,25] , retinal detachment [26] , uveitis [27,28] , dry eye [29,30] , and other ocular surface diseases [31] . Analyses have been performed on tear fluid [23,[29][30][31][32] , aqueous humor [24,25,33,34] , vitreous humor [20,26,27,35,36] , cornea [37][38][39] , conjunctiva [40] , and lens [41,42] samples.…”
Section: Metabolomics In Ophthalmologymentioning
confidence: 99%
“…However, a correlation with disease stage has been shown for diabetic retinopathy [21] , as well as age-related macular degeneration [18,19] . Similar studies have been conducted in cancer research, one of the largest areas of metabolomics research; preserved blood and urine samples have been used to metabotype progressive and/or relapsing patients.…”
Section: Metabolomics In Glaucomamentioning
confidence: 99%
“…However, suboptimal sensitivity can be a major impediment to clinical implementation, because clinicians can be reluctant to trust results from point-of-care testing, and/or the need for back up laboratory test confirmation continues. 2 We are aware of 3 diagnostic accuracy studies of the AdenoPlus point-of-care test. The study we cited in our editorial 3 found a sensitivity of 39.5% in a hospital eye emergency department, Sambursky et al 4 found a much higher sensitivity of 85% to 90% (depending on the reference standard used) in ophthalmology private practices and academic centers, whereas Holtz et al 5 found a sensitivity of 50% in acute eye care clinics.…”
mentioning
confidence: 99%
“…The results of the AMD biomarker found in the blood were different when compared with this study's results. 2 Second, it was noted that this study enrolled 30 controls and 90 patients with AMD; however, did the authors calculate the sample size? In their previous studies, they enrolled a total of 396 patients to test the plasma metabolomic profile in patients with AMD by nuclear magnetic resonance spectroscopy.…”
mentioning
confidence: 99%
“…Although certain TCA-related organic acids were analyzed in the samples from Osborn et al, 28 the putative metabolite identifications still need to be confirmed by LC/MS and authentic standard samples. 29 Our AH quantitative analysis of AMD fingerprints, with particular interest in glucose-related metabolites, presented both similarities and differences with previous articles. First, AH showed no significant increase in lactate concentrations, which is the preferable production of aerobic glycolysis in the retina.…”
Section: Discussionmentioning
confidence: 53%